AN ANALYSIS OF STUDENTS’ LEARNING STYLES IN WRITING RECOUNT TEXT ABILITY (A Study at the Eleventh Grade Students of SMA Negeri 1 Kolang) - Nita Bernike Pardede (JURNAL LINER (Language Intelligence and Educational Research), 2018)
Abstract: The aims of the research is to know the learning styles which are suitable of students’ at the eleventh grade of SMA Negeri 1 Kolang, and how are students’ achievement in writing recount text ability based on their learning styles. The research is used mixed method; that is combination of qualitative and quantitative. The informants are 9 students based their academic achievement. The data is collected by questionnaire for students’ learning styles and test in writing recount text. An analysis of students in learning styles, there are 3 learning styles that is auditory, visual, and kinesthetic. For auditory, one of them got 91 its categorized very good, visual one of them got 72 its categorized good, and kinesthetic one of them got 72 its categorized good. Writing recount text the result got score is good. The state can be auditory learning styles better than visual and kinesthetic learning styles. Keywords: Learning Styles, Writing, Recount Text